“La dislexia en el proceso de enseñanza - aprendizaje” - Ganchala Suntasig, Mayra Elizabeth (2023)
The didactic pedagogical process is developed as the space, in which students are the ones who build knowledge from reading, contributing their experiences and reflecting on them, exchanging their view points with their classmates and the teacher. However, within this process there are students what confuse letters, have reading problems and present mirror writing, these aspects affect the reading behavior functionality and it prevents to the subject extracts from correctly and efficiently written information and, therefore, affect to their academic, personal and social adaptation. The research pretends to identify dyslexia for determining the impact on the EGB seventh year children teaching-learning process, parallel "B" from "14 de Octubre - Vicente Rocafuerte" Educational Unit, from Pujilí canton, Cotopaxi province, school year 2022-2023. It was performed by qualitative and quantitative research, inductive method, with the interview technique and the psycho-pedagogical test, each one with its respective instrument, the interview guide and the questionnaire. The data was collected to support and justify the purpose of the research with the got information from the researched subjects. Regarding the results, they were analyzed the collected information from the informants, so, were extracted the keywords, categories and subcategories. Therefore, among the main results, they are noted the information taken from the Specific Dyslexia Exploration Test application, which is divided into two areas, the first called reading level that it was got, what students 42% have marked errors as regards to the identification letter names and sounds, and different levels syllables pronunciation, including phonograms and diphthongs. On the other hand, in the test second area called specific errors, it was evidenced that students 38% have reading difficulties, therefore, they confuse and invert letters and syllables within words. This project is essential because it allows, what teachers know the dyslexia disorder, since it is the premature diagnosis subject responsible this learning difficulty in the childhood. In this sense, the teacher must be updated, as regards methodological strategies for the backing the children's literacy development and avoid students academic regression with dyslexia.